Professional Alignment in Primary Education: The Interplay Between Teacher Certification, Workload, and Assignment Linearity - Dwi Mahya Sari; Dina Martha Fitri; Rangga Firdaus (Al-Qalam Institue, 2026)
The transition from the 2013 Curriculum to the Merdeka Curriculum in Indonesia, coupled with the issuance of the Ministerial Regulation No. 11/2025 on Teacher Workload and Ministerial Decree No. 222/O/2025 on Teacher Certification Linearity, has significantly affected the assignment of linear English teachers as classroom teachers in elementary schools. This systematic literature review aims to analyze the impact of certification and workload policies on English teacher assignments, learning coverage and quality, and curriculum development recommendations integrating educational technology. Following the PRISMA 2020 protocol, 44 studies were selected from 1,248 records across Google Scholar, SINTA, GARUDA, Scopus, and ERIC (2013–March 2026) and analyzed using thematic synthesis. Findings reveal that linearity policies create opportunities but compel teachers to assume roles beyond their specialization; workload fulfillment often reduces English instructional time; teaching quality is affected by time constraints and underutilization of technology; and curriculum transition increases autonomy yet leaves assignment challenges unresolved. Integrating educational technologies such as Learning Management Systems, AI-assisted tools, augmented reality, and blended learning can expand English learning coverage while alleviating teacher workload. The study recommends innovative curriculum models emphasizing teacher collaboration, community of practice, and technology integration to optimize the contributions of linear English teachers without compromising student learning hours.